The Effect of Cognitive-Behavioral Intervention on Self-Care Behaviors and Blood Pressure Control in Patients with Primary Hypertension - Elham Ebrahimidorcheh; Mahin Nematollahi; Ahmadali Eslami (Journal of Education and Community Health)
Aims: Adopting self-care behaviors in patients with hypertension is one of the most effective ways to control blood pressure. The present study was designed to evaluate the effect of the cognitive-behavioral intervention on self-care behaviors and blood pressure control. Materials & Methods: This clinical trial study conducted in 2019 on patients over 30-years with primary hypertension in Dorcheh 1 Health Center in Isfahan, Iran. Patients were randomly selected from 100 people with high blood pressure and divided into two groups, Intervention, and control. In addition to receiving routine care, the intervention group participated in a cognitive-behavioral educational intervention program. The required information was collected using background, cognitive, and behavioral information questionnaires related to blood pressure control, (with optimal validity and reliability) before and one month after the intervention. Data were analyzed by SPSS 25 software using statistical methods of Chi-Square, Fisher exact test, Mann-Whitney, ANCOVA, t-test. Findings: After the intervention, the mean scores of cognitive and behavioral variables in the intervention group were significantly different from the control group. Also, systolic blood pressure decreased significantly in the experimental group (p<0.05). Conclusion: Cognitive-behavioral intervention improves systolic blood pressure and improved the level of cognitive and behavioral variables associated with blood pressure control in patients.